PERBANDINGAN MINAT BELAJAR PAI DAN BUDI PEKERTI SISWA LULUSAN MADRSAH TSANAWIYAH (MTs) DAN SEKOLAH MENENGAH PERTAMA (SMP) DI SMA NEGERI 1 BANUHAMPU KAB. AGAM - Khairani Khairani; Bambang Trisno (ADISAM PUBLISHER, 2025)
This research was motivated by the discovery that learning occurred more actively among students from junior high school graduates than students from madrasah graduates. This is proven by the seriousness of students in participating in the teaching and learning process and the enthusiasm of students in asking questions about PAI and Moral Education subject matter. This is of course a problem that must be resolved. Because students who graduate from MTs should be superior to students who graduate from junior high school. The aim of this research is to find out a significant comparison of interest in learning PAI and Characteristics of students graduating from Madrasah Tsanawiyah with junior high school graduates at State High School 1 Banuhampu Kab. Agam. The type of research used in thisresearch is comparative with a quantitative approach. The population is all class The sample in this study used a Probability Sampling technique using Cluster Random Sampling, and 3 classes were sampled, with details of 34 MTs graduate students and 34 junior high school graduate students. Data was collected through questionnaires, observation and documentation analyzed using descriptive tests and paired sample t tests. Based on the results of the research that has been carried out, the results show that there is a comparison of interest in learning PAI and Characteristics of students who graduated from MTs and SMP, which is proven by the results of the Paired sample t test where the t value > t table, namely 2.067 > 1.998. Based on these values, it can be seen that the t-calculated value is greater than the t-table, which means that there is a comparison of interest in learning PAI and Characteristics of students who graduated from MTs and students who graduated from middle school class X at SMA Negeri 1 Banuhampu, so Ha was accepted. MTs graduate students are more likely to have a good interest in learning than junior high school graduate students.